Temporal patterns and mechanisms of epilepsy surgery failure. Issue 5 (15th April 2013) - Najm, Imad; Jehi, Lara; Palmini, Andre; Gonzalez‐Martinez, Jorge; Paglioli, Eliseu; Bingaman, William
Summary Epilepsy surgery is an accepted treatment option in patients with medically refractory focal epilepsy. Despite various advances in recording and localization noninvasive and invasive techniques (including electroencephalography (EEG), magnetic resonance imaging (MRI), positron emission tomography (PET), single photon emission computed tomography (SPECT), magnetoencephalography (MEG), subdural grids, depth electrodes, and so on), the seizure outcome following surgical resection remains suboptimal in a significant number of patients. The availability of long‐term outcome data on an increasing number of patients suggests two major temporal patterns of seizure recurrence (early vs. late) that implicate the following two different mechanisms for seizure recurrence: (1) a failure to either define/resect the epileptogenic zone, and (2) the nonstatic nature of epilepsy as a disease through the persistence of proepileptic cortical pathology. We describe the temporal patterns of epilepsy surgery failures and discuss their potential clinical, histopathologic, genetic, and molecular mechanisms. In addition, we review predictors of successful surgical interventions and analyze the natural history of epilepsy following surgical intervention. We hypothesize that the acute/early postoperative failures are due to errors in localizing and/or resecting the epileptic focus, whereas late recurrences are likely due to development/maturation of a new and active epileptic focus (de novo epileptogenesis).